Characteristics of Lactic Acid Bacteria Isolated from Gastrointestinal Tract of Cemani Chicken and Their Potential Use as Probiotics - Siti Nur Jannah; Achmad Dinoto; Komang Gede Wiryawan; Iman Rusmana (Media Peternakan, 2014)
The aims of this study were to screen and characterize lactic acid bacteria (LAB) isolated from gastrointestinal (GI) tract of Cemani chicken, one of Indonesian local chicken and to investigate their potential use as probiotics. LAB were isolated from GI tract using MRSA and GYPA media and incubated anaerobically. Selected LAB were determined their probiotic properties with several assays. Identification of selected LAB was based on 16S rDNA sequences, morphological and biochemical characteristics. Ninety five bacteria  were isolated and characterized as lactic acid bacteria (Gram positive, catalase negative, non sporeforming and acid producing). Twenty four isolates of LAB demonstrated antimicrobial activity against Escherichia coli JCM 1649 and Salmonella enteritidis B2586, and three selected isolates, i.e. CCM011, CSP004, and CVM002 showed the highest inhibition activity. The isolates had characters of high cell surface hydrophobicity and inter-isolate coaggregation ability of LAB, high survival at low pH, high  phytase and protease activity (but no amylase and lipase activity), weak coaggregation with pathogen and no resistance to the examined antibiotics. The isolates were identified based on sequence analysis of 16S rRNA gene as Lactobacillus salivarius, however, each isolate had different profiles of sugar fermentation. Therefore the three LAB isolates had potential application as probiotics for chicken.Key words: Cemani chicken, gastrointestinal tract, lactic acid bacteria, probiotic